The Role of Documentary Production in Radio Broadcasting - Zahra, Siti; Kustiawan, Winda; Hasibuan, Muhammad Rifky Azhar (Jurnal Riset Ilmu Pendidikan, 2025)
Documentary films are a form of visual work that serves to document reality, educate, and inspire their audience. In the fast-paced information era, documentaries have become an important tool for conveying facts and explaining complex social issues. The production process of documentaries involves pre-production, production, and post-production stages, where good management is essential to achieve effective results. The types of documentaries categorized by Bill Nichols reflect various approaches in storytelling, whether through narration or observation. Additionally, documentary films play a role in the construction of social reality, which is the result of collective interaction and knowledge within society. Film communities also contribute to the development of documentary works, creating spaces for collaboration and innovation. Therefore, a deep understanding of the production process and social context is crucial for documentary filmmakers to raise awareness and promote social change.